Jasmine Sanchez Photograph Collage - Sanchez, Jasmine:::::::::
Jasmine Sanchez started Vessel Athletics during sophomore year at San José State University. The company launched an event called The Run Continues to support small businesses, local restaurants, and those affected by COVID-19.(COVID-19)